Comparing Human Amniotic Allograft and Standard Wound Care When Using Total Contact Casting in the Treatment of Patients with Diabetic Foot Ulcers. (June 2019) - Thompson, Patricia; Hanson, Darlene S.; Langemo, Diane; Anderson, Julie
ABSTRACT: OBJECTIVE: This prospective, randomized study compared two treatments for diabetic foot ulcers: total contact cast and a skin substitute versus total contact cast and standard wound care. PARTICIPANTS: Researchers screened 270 adult outpatients in a Midwestern wound care clinic for inclusion. Adults 18 years or older with type 1 or 2 diabetes and a diabetic foot ulcer located on the plantar surface larger than 0.5 cm 2 in area were invited to participate if they had not demonstrated a 50% reduction in wound area following 4 weeks of standard treatment. Thirteen patients were randomized into two intervention groups. The majority of the participants had type 2 diabetes. INTERVENTIONS: Group A treatment: total contact cast and a skin substitute (human amniotic allograft); group B treatment: total contact cast and standard wound care. OUTCOME MEASURES: Mean ulcer surface area, time to closure, recurrence rates, satisfaction with total contact casting, infection, and hemoglobin A1c were measured. RESULTS: The majority of participants experienced wound closure during the course of the study (92.3%). Two participants did not achieve closure, both of whom had Charcot foot. Group A, which had a higher mean hemoglobin A1c at study outset, experienced a longer mean time to closure (29.50 days) compared with group B (26.20 days). The 90-day recurrence rates were different for the two groups, with only one recurrence for group A (14.29%) but five recurring ulcers in group B (83.33%). CONCLUSIONS: Although significance was not established because of sample size, there was a definite trend toward significance that merits further investigation with human amniotic allograft.